The Structural Architecture of an Infectious Mammalian Prion Using Electron Cryomicroscopy - Vázquez-Fernández,E; Vos,MR; Afanasyev,P; Cebey,L; Sevillano,AM; Vidal,E; Rosa,I; Renault,L; Ramos,A; Peters,PJ; Fernández,JJ; van,Heel M; et al. (PLOS Pathogens, 2016)
The structure of the infectious prion protein (PrPSc), which is responsible for Creutzfeldt-Jakob disease in humans and bovine spongiform encephalopathy, has escaped all attempts at elucidation due to its insolubility and propensity to aggregate. PrPSc replicates by converting the non-infectious, cellular prion protein (PrPC) into the misfolded, infectious conformer through an unknown mechanism. PrPSc and its N-terminally truncated variant, PrP 27-30, aggregate into amorphous aggregates, 2D crystals, and amyloid fibrils. The structure of these infectious conformers is essential to understanding prion replication and the development of structure-based therapeutic interventions. Here we used the repetitive organization inherent to GPI-anchorless PrP 27-30 amyloid fibrils to analyze their structure via electron cryomicroscopy. Fourier-transform analyses of averaged fibril segments indicate a repeating unit of 19.1 Å. 3D reconstructions of these fibrils revealed two distinct protofilaments, and, together with a molecular volume of 18,990 Å3, predicted the height of each PrP 27-30 molecule as ~17.7 Å. Together, the data indicate a four-rung β-solenoid structure as a key feature for the architecture of infectious mammalian prions. Furthermore, they allow to formulate a molecular mechanism for the replication of prions. Knowledge of the prion structure will provide important insights into the self-propagation mechanisms of protein misfolding.